Young children conform more to norms than to preferences. - Leon Li; Bari Britvan; Michael Tomasello (PLoS ONE)
As members of cultural groups, humans continually adhere to social norms and conventions. Researchers have hypothesized that even young children are motivated to act conventionally, but support for this hypothesis has been indirect and open to other interpretations. To further test this hypothesis, we invited 3.5-year-old children (N = 104) to help set up items for a tea party. Children first indicated which items they preferred but then heard an informant (either an adult or another child) endorse other items in terms of either conventional norms or personal preferences. Children conformed (i.e., overrode their own preference to follow the endorsement) more when the endorsements were framed as norms than when they were framed as preferences, and this was the case whether the informant was an adult or another child. The priority of norms even when stated by another child opposes the interpretation that children only conformed in deference to adult authority. These findings suggest that children are motivated to act conventionally, possibly as an adaptation for living in cultural groups.